A rotational friction damper-brace for seismic design of resilient framed structures. (1st July 2022) - Javidan, Mohammad Mahdi; Kim, Jinkoo
Abstract: In the present study, a ductile bracing system is proposed which has a rotational friction damper joint with an eccentricity from the diagonal of the bay. Similar to other seismic energy dissipation devices, the developed system can be used for seismic design of new structures, where other structural elements remain elastic during earthquakes, as well as for seismic retrofit of existing structures. The structural behavior of this system is studied thoroughly using theoretical approaches and a seismic design procedure is provided. The formulations are verified by establishing an analysis model of the system and comparing the theoretical and analytical results. A ductility-based design procedure is provided for structures using this system and an illustrative three-dimensional structure is designed and analyzed in detail using various analysis methods. The results show that the proposed damper-brace system and the design process can be efficiently used in practice. Highlights: This study develops a ductile bracing system with a rotational friction damper joint. Theoretical formulation was derived which are verified by establishing an analysis model of the system. A ductility-based design procedure is provided and an example structure is designed and analyzed in detail. The results show that the proposed damper-brace system and the design process can be efficiently used in practice.